Integrative transcript to proteome analysis of barley during Ramularia collo-cygni leaf spot development identified several proteins that are related to fungal recognition and infection responses - Lemcke, René; Kamble, Manoj; Schneider, Sebastian; Lyngkjær, Michael F.; Radutoiu, Simona; Wienkoop, Stefanie (Frontiers in Plant Science, 2024)
Ramularia leaf spot disease (RLS) is a growing threat to barley cultivations; however, with no substantial resistance identified to date. Likewise, the understanding of the life-style of Ramularia collo-cygni (Rcc) and the prediction of RLS outbreak severity remains challenging, with Rcc displaying a rather untypical long endophytic phase and a sudden change to necrotrophic life style. The aim of this study was to provide further insights into the defense dynamics during different stages of colonization and infection in barley to identify potential targets for resistance breeding. To use the strength of proteomics in comprehending plantpathogen interactions, we performed an integrative analysis of a published transcriptome dataset with a parallel generated proteome dataset. Therefore, we included two spring barley cultivars with contrasting susceptibility to Rcc as well as two fungal isolates causing different levels of RLS symptoms. Interestingly, early responses in the pathogen recognition phase of the host were driven by strong responses differing between isolates. An important enzyme in this process were a Xylanase inhibitor, protecting the plant from cell wall degradation by the fungal xylanase. At late time points the differences are driven by cultivar specific responses, affecting mostly features contributing to pathogenesis-and senescence-related pathways or photosynthesis and supporting the hypothesis of a hemi-biotrophic lifestyle of Rcc with slight